Quantitative analysis of cortical pyramidal neurons after corpus callosotomy - Jacobs, Bob; Creswell, Johanna; Britt, Jonathan P.; Ford, Kevin L.; Bogen, Joseph E.; Zaidel, Eran (Annals of neurology, 2003)
This study quantitatively explored the dendritic/spine extent of supragranular pyramidal neurons across several cortical areas in two adult male subjects who had undergone a callosotomy several decades before death. In all cortical areas, there were numerous atypical, supragranular pyramidal neurons with elongated “tap root” basilar dendrites. These atypical cells could be associated with an underlying epileptic condition and/or could represent a compensatory mechanism in response to deafferentation after callosotomy. Ann Neurol 2003